Presentasi Visual dalam Tata Kemas Sego Pincuk Terhadap Persepsi Gastronomi dan Kenikmatan - Andika Agung Sutrisno (MAVIS : Jurnal Desain Komunikasi Visual, 2024)
Food consumption has evolved from a basic human need to a lifestyle choice. Exploration of the role of packaging in shaping consumer perceptions of taste preferences, with a focus on ready-to-eat foods in banana leaf containers known as "pincuk". Sego Pincuk attracts attention not only for its distinctive taste, but also for its simple visual presentation. The use of banana leaves as natural packaging reflects local wisdom in utilizing resources sustainably and enhancing the gastronomic experience with natural sensations. Gastronomy not only includes the taste and texture of food, but also explores the history, traditions, and values ​​associated with food consumption within a culture. Sego Pincuk's visual presentation plays an important role in forming consumers' initial perceptions of the dishes that buyers will choose. The research uses a qualitative descriptive approach to understand the impact of visual presentation on gastronomy and aesthetic experiences due to visual perception. Direct observations, interviews, and content analysis were carried out to examine the sego pincuk phenomenon to gain holistic insight into how visual packaging presentation influences consumer responses and preferences. The visual presentation of traditional packaging acts as an emotional link for consumers to their cultural heritage and culinary preferences. Emotional ties are important to maintain and promote traditional cultural values ​​in a culinary experience rich with authentic flavors and aesthetics.